2013
DOI: 10.1038/emm.2013.89
|View full text |Cite
|
Sign up to set email alerts
|

In vivo action of IL-27: reciprocal regulation of Th17 and Treg cells in collagen-induced arthritis

Abstract: Interleukin (IL)-27 is a novel cytokine of the IL-6/IL-12 family that has been reported to be involved in the pathogenesis of autoimmune diseases and has a pivotal role as both a pro- and anti-inflammatory cytokine. We investigated the in vivo effects of IL-27 on arthritis severity in a murine collagen-induced arthritis (CIA) model and its mechanism of action regarding control of regulatory T (Tregs) and IL-17-producing T helper 17 (Th17) cells. IL-27-Fc-treated CIA mice showed a lower severity of arthritis. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 49 publications
2
54
1
1
Order By: Relevance
“…By contrast, a recent study found that IL-27 could be beneficial by inhibiting osteoclastogenesis [19]. This study corroborates the findings of other ones that consider IL-27 to be an anti-inflammatory factor [20] and a possible positive inflammatory regulator in arthritis [21], multiple sclerosis [22], and even cancer [23]. IL-27 is a cytokine that probably acts in the regulation of bone homeostasis.…”
Section: Discussionsupporting
confidence: 69%
“…By contrast, a recent study found that IL-27 could be beneficial by inhibiting osteoclastogenesis [19]. This study corroborates the findings of other ones that consider IL-27 to be an anti-inflammatory factor [20] and a possible positive inflammatory regulator in arthritis [21], multiple sclerosis [22], and even cancer [23]. IL-27 is a cytokine that probably acts in the regulation of bone homeostasis.…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, neutrophils were also reduced after anti-IL-17 treatment, confirming the role of IL-17 in neutrophil recruitment to infected organs in parallel to induction of NO production by macrophages, as previously shown by our group. The regulatory role of IL-27 on IL-17 response has been demonstrated under autoimmune inflammatory conditions, such as in experimental autoimmune encephalomyelitis (12) as well as in collagen-induced arthritis (31). Here, we suggest that IL-27 plays a major role as an important regulatory cytokine implicated in infectious disease.…”
Section: Discussionmentioning
confidence: 78%
“…and PD-1 [133], or LAG3 (on human Treg) [134] on their cell surface. Jeon et al [135], have reported that B. breve activates intestinal CD103 + DCs to produce IL-10 and IL-27 via the TLR2/MyD88 pathway thereby inducing IL-10-producing Tr1 cells in the large intestine and thus prevents intestinal inflammation.…”
Section: Activation Of Treg Associated Moleculesmentioning
confidence: 99%